KATEGORI DESAIN SEISMIK WILAYAH KOTA PALEMBANG BERDASARKAN SNI 03-1726-2012 DENGAN MENGGUNAKAN PETA HAZARD GEMPA INDONESIA 2010 - sapta sapta; Sari Farlianti (Universitas IBA Palembang, 2017)
Seismic Design category described the Risk level of Seismicity are used as the basis for the selection of the Moment Frame Structure that will be used in the implementation of the design of structures that use the SNI 03-2847-2013. KDS in SNI 03-1726-2012, classified into three levels respectively, namely; Low (SDC A and B), intermediate (SDC C) and high (SDC D, E and F). Classification of SDC are determined based on the values of the SDS and the SD1 is the spectral response acceleration parameter design on a short period and a period of 1,00 second. The value of the SDS and the SD1 is determined the condition of soil density (soft, medium or hard) on the regions reviewed. From the results of the analysis performed using data on Earthquake Hazard Map 2010 by using application designs spectra and on the website of http://puskim.pu.go.id obtained the value soil for SDS Badger, medium and hard respectively worth 0.43; 0.278; 0.209 SD1 and 0.361; 0.234; 0.179, so it can be inferred that the Palembang area with a high level of risk, namely KDS D, which in the planning of the structure requires using the structure of Special Moment Frame (SRPMK) which refers to the SNI 03-2847-2013. Key words: Seismic Design category (SDC), Map of the earthquake area, Moment Frame